Targeting transmembrane-domain-less MOG expression to platelets prevents disease development in experimental autoimmune encephalomyelitis - Cai, Yuanhua; Schroeder, Jocelyn A.; Jing, Weiqing; Gurski, Cody; Williams, Calvin B.; Wang, Shaoyuan; Dittel, Bonnie N.; Shi, Qizhen (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease of the central nervous system with no cure yet. Here, we report genetic engineering of hematopoietic stem cells (HSCs) to express myelin oligodendrocyte glycoprotein (MOG), specifically in platelets, as a means of intervention to induce immune tolerance in experimental autoimmune encephalomyelitis (EAE), the mouse model of MS. The platelet-specific αIIb promoter was used to drive either a full-length or truncated MOG expression cassette. Platelet-MOG expression was introduced by lentivirus transduction of HSCs followed by transplantation. MOG protein was detected on the cell surface of platelets only in full-length MOG-transduced recipients, but MOG was detected in transmembrane-domain-less MOG1-157-transduced platelets intracellularly. We found that targeting MOG expression to platelets could prevent EAE development and attenuate disease severity, including the loss of bladder control in transduced recipients. Elimination of the transmembrane domains of MOG significantly enhanced the clinical efficacy in preventing the onset and development of the disease and induced CD4+Foxp3+ Treg cells in the EAE model. Together, our data demonstrated that targeting transmembrane domain-deleted MOG expression to platelets is an effective strategy to induce immune tolerance in EAE, which could be a promising approach for the treatment of patients with MS autoimmune disease.